Sociological Aspects of Economic Growth - Hoselitz, Bert F. (Glencoe, Ill.: Free Press, 1960)
The author seeks to construct a theoretical model which he believes will be useful in depicting the transition of "traditional" societies to a more "modern" form of social organization.
Includes bibliography.
osa;09/04/18
Loans
Keywords: Economic development; Social history